Learning from the Bhopal disaster to improve process safety management in Singapore - Goh, Yang Miang; Tan, S.; Lai, K. (Institution of Chemical Engineers, 2015)
The Singapore process industry is mainly made up of chemical and energy companies such as Mitsui Chemicals, Clariant, Exxon Mobil, Shell, Sumitomo, Petrochemical Corporation of Singapore and Infineum. Majority of these companies are located on Jurong Island, southwest of Singapore. Jurong Island houses nearly 100 leading petroleum, petrochemicals and specialty chemicals companies and the total investment is about S$42 billion in total. With a land surface area of only 716 km2 and a high concentration of process plants, the Singapore government places strong emphasis on safety and risk management. In this paper, four process industry veterans from the government, academic and private sectors were interviewed. Through the interviews, the authors sought to understand the veterans' perspectives on lessons that the Singapore process industry should learn from the Bhopal disaster. The veterans expanded their thoughts beyond the Bhopal disaster and provided many insights and suggestions critical to process safety management in Singapore and other countries. A systemic model of process safety management was derived from the interviews and key elements of operational process safety management were identified. In addition, a research agenda was identified based on the inputs from the veterans.